Zimbabwean farmers go east and west - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Angolan government has allocated 10,000 hectares of arable land in Huambo province for Zimbabwean commercial farmers who have abandoned their land due to the political situation in Zimbabwe. These measures should create jobs and stimulate the...